Altered Activity of SK Channel Underpins Morphine Withdrawal Relevant Psychiatric Deficiency in Infralimbic to Accumbens Shell Pathway - Qu, Liang; Wang, Yuan; Ge, Shun-Nan; Li, Nan; Fu, Jian; Zhang, Yue; Wang, Xin; Jing, Jiang-Peng; Li, Yang; Wang, Qiang; Gao, Guo-Dong; He, Shi-Ming; et al. (Frontiers in Psychiatry, 2019)
Drug addiction can be viewed as a chronic psychiatric disorder that is related to dysfunction of neural circuits, including reward deficits, stress surfeits, craving changes and compromised executive function. The nucleus accumbens (NAc) plays a crucial role in regulating craving and relapse, while the medial prefrontal cortex (mPFC) represents a higher cortex projecting into the NAc that is active in the management of executive function. In this study, we investigated the role of the small conductance calcium-activated potassium channels (SK channels) in NAc and mPFC after morphine withdrawal. Action potential (AP) firing of neurons in the NAc shell was enhanced via the downregulations of the SK channels after morphine withdrawal. Furthermore, the expression of SK2 and SK3 subunits in the NAc was significantly reduced after 3 weeks of morphine withdrawal, but was not altered in the dorsal striatum. In mPFC, the SK channel subunits were differentially expressed. To be specific, the expression of SK3 was upregulated, while the expression of SK2 was unchanged. Furthermore, the AP firing in layer 5 pyramidal neurons of the infralimbic (IL) cortex was decreased via the upregulations of the SK channel related tail current after 3 weeks of morphine withdrawal. These results suggest that the SK channel plays a specific role in reward circuits following morphine exposure and a period of drug withdrawal, making it a potential target for the prevention of relapse.